Overlapping committee membership and cost of equity capital - Bhuiyan MBU; Cheema MA (Elsevier B V, 2024)
This study examines the association between overlapping committee membership and the cost of equity capital among listed companies in Australia. Overlapping committee membership occurs when a director serves on multiple supervisory committees concurrently. To the extent overlapping committee membership reduces information asymmetry, improves financial reporting quality, and consequently reduces the overall risk of the firms, we expect a negative relationship between overlapping membership and the cost of equity capital. Consistent with our argument, we find a positive impact of overlapping committee membership and provide evidence that firms with overlapping committee membership have a lower cost of equity capital. Furthermore, our results indicate that the positive impact of overlapping committee membership on the cost of equity capital is more evident when overlapping committee members are non-busy directors.
Keywords: Overlapping committee membership; Cost of equity capital; Non-busy directors